TANGGUNG JAWAB MASKAPAI PENERBANGAN ATAS KEAMANAN PENUMPANG DALAM RUTE PENERBANGAN NON IZIN DI TINJAU DARI UNDANG-UNDANG REPUBLIK INDONESIA NOMOR 1 TAHUN 2009 TENTANG PENERBANGAN - Mhd. Subhi Solih Hasibuan; Tan Kamello; Hasim Purba; Rosnidar Sembiring (USU LAW JOURNAL, 2017)
ABSTRACT Any air flight accidents always result in losses for passengers either moral or materill which of course gave birth to prolonged legal issues, particularly with regard to the legal responsibility of the airline or carrier (carrier) against passenger and owner of the goods, as the parties to the agreement as well as the carriage as a consumer, especially if an accident on a flight without permission. The issue raised in this research, i.e. how legal consequences for businessmen who do tort related infringement safety for passengers on the flight routes of non consent, the responsibility over the security of airline passengers in the flight route to non permission, and the form of compensation the airline cannot satisfy the security factor for passengers on the flight routes of non consent.   Key Words: Responsibility, Aviation, Non Consent